Analisis Clustering Kepuasan Pelanggan Bengkel Mobil Auto Muara Baru Menggunakan Metode K-Means - Herdiansyah, Roydido; Suryadi, Sudi; Irmayanti, Irmayanti (Journal of Computer Science and Information System(JCoInS), 2025)
This study aims to analyze customer satisfaction of Muara Baru Auto Repair Shop by using K-Means clustering method. Customer satisfaction is a crucial factor in maintaining loyalty and improving service quality in the automotive industry. The Data was collected through surveys involving customers who had used the workshop services, and then analyzed using the k-Means algorithm to identify patterns and clusters in satisfaction levels. The results of the analysis show that there are several clustering that reflect variations in customer satisfaction levels, providing important insights into service aspects that need to be improved as well as areas that have met customer expectations. These findings indicate that the K-Means method is effective in analyzing customer satisfaction and can be used as a basis for workshop management to formulate service improvement strategies to better meet customer expectations.